Fire, pestilence and the extractive economy: cultural policy after cultural policy. Issue 1 (1st January 2021) - Pacella, Jessica; Luckman, Susan; O'Connor, Justin
ABSTRACT: Australia has witnessed long-standing cuts in the arts and culture federal budget. Most recently, the disappearance of the arts portfolio into a "super-ministry" along with infrastructure, transport, regional development and communications further signals the lack of support, both ideologically through public rhetoric, and financially through (absent) support packages, the current federal government holds towards the arts and arts workers. This paper accounts for how such ideological fractures have underserved freelancers, casuals, temporary and part-time workers in the arts who missed out on the critical initial support packages, and how state governments were more willing to make up for this initial shortfall. This paper further accounts for how the federal government lacks the necessary understanding of working patterns of those engaged in creative occupations, and over emphasizes funding bailouts for primary industry. This also has broader implications for how women are disproportionately impacted by sectors the federal government chooses to support.